2007
DOI: 10.1111/j.1365-2893.2007.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of 2 years of interferon treatment in patients with chronic delta hepatitis

Abstract: High dose interferon treatment for 1 year is the only established treatment for chronic hepatitis D, but it is associated with a high relapse rate after treatment discontinuation. In this study, patients were treated with 10 MU interferon alpha 2b, thrice weekly for 2 years. Twenty-three patients were recruited and 15 completed the 2-year treatment and 6 months follow-up periods. Treatment response was assessed biochemically [normal alanine aminotransferase (ALT)], virologically (undetectable hepatitis D virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 14 publications
(15 reference statements)
2
48
1
Order By: Relevance
“…These authors determined whether long-term therapy is more efficacious than 1-year therapy. Their results showed that both long-term and 1-year therapy had the same outcomes; this finding is similar to that of another Turkish study (1). Therefore, if there is no virologic response, then therapy should be discontinued after a year; this will help avoid causing unnecessary inconvenience to patients and reduce the costs incurred by health agencies.…”
supporting
confidence: 72%
“…These authors determined whether long-term therapy is more efficacious than 1-year therapy. Their results showed that both long-term and 1-year therapy had the same outcomes; this finding is similar to that of another Turkish study (1). Therefore, if there is no virologic response, then therapy should be discontinued after a year; this will help avoid causing unnecessary inconvenience to patients and reduce the costs incurred by health agencies.…”
supporting
confidence: 72%
“…Yurdaydin et al also compared patients receiving 1-year and 2-year treatments in Turkey and reported that 2 years of treatment does not appear to increase sustained response rates in comparison with 1 year of treatment (9). However, Gunsar et al reported that 2-year treatment is better than 1-year treatment (10).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated 46 CDH patients, a large group for CDH, and observed that there is not much difference between 1-year and 2-year treatments in terms of virological, histological, and biochemical responses. Long-term PEG-IFN therapy might be more efficacious (9,11,12). Available trials indicate that high doses of interferon and a long duration of therapy were associated with a better biochemical response and improvement in liver histology (11).…”
Section: Discussionmentioning
confidence: 99%
“…This was attended by improvement of liver histology (initially cirrhosis, after 10 years no abnormalities) [38] . Interestingly Yurdaydin et al [39] could not find a benefit for IFN treatment over 2 years instead of 1 year. However long-term data (12 years) showed a benefit of high-dose IFN α therapy (9 million units three times per week) with even regression of advanced hepatic fibrosis [40] .…”
Section: Treatment Of Delta Hepatitismentioning
confidence: 99%